(untitled) (Physical Education, Health and Social Sciences, 2026)
Background/Purpose: A health system under pressure - Pakistan struggles to advance care standards and safeguard patients, especially within the uneven landscape of Khyber Pakhtunkhwa. Because resources are tight, progress in quality improvement falters across many facilities there. Instead of assuming solutions fit all, researchers looked closely at how current methods fall short. By analyzing real conditions on the ground, they sought patterns behind failures and openings for change. Rather than copying models from wealthier regions, attention turned to locally relevant fixes. One key aim emerged - not just to map weaknesses but to rank practical steps forward. Through structured review, gaps in policy, training, and oversight came into view. While some efforts exist, most lack coordination or sustained support. To answer how safer, better care might take root despite limits, insights were grounded in frontline realities. From clinics in remote valleys to urban hospitals, variation shapes what works - and what does not. Methods: From thirty public and private hospitals in Peshawar, KP, 385 health staff took part in a mixed-methods analysis. The survey instrument followed the WHO framework on patient safety culture; responses came through a standardized tool previously tested for consistency. Interviews without fixed formats reached select participants: forty physicians, sixty nurses, twenty managers, ten policy figures. To check internal consistency, Cronbach’s alpha showed a value of 0.84. Analysis occurred in SPSS version 26 - methods included summaries, chi-square evaluations, alongside logistic modeling where appropriate. Though planned separately, qualitative insights supported numerical trends observed across sites. A method of thematic review shaped the handling of spoken responses, guided by a structure in six parts. Following organized steps, scrutiny of official guidelines took place alongside detailed looks at four medical centers: one named Khyber Teaching Hospital, another called Lady Reading Hospital, a third located in Karachi under the Indus name, also one honoring Shaukat Khanum focused on cancer care. Results: The most frequently reported patient safety event was poor communication (50%), followed by medication errors (48%). Regarding quality improvement, overcrowding/insufficient beds (45%) and inadequate training (42%) were the two major barriers identified. Staff training and development (55%) and Electronic Health Record (EHR) implementation (50%) were ranked as the top priority strategies. Chi-square analysis revealed a statistically significant association between hospital type (public vs. private) and frequency of patient safety incidents (χ²=14.27, df=3, p=0.003). Logistic regression identified weak leadership (OR=2.41, 95% CI: 1.52–3.82, p<0.001) and inadequate training (OR=1.89, 95% CI: 1.23–2.91, p=0.004) as independent predictors of frequent safety incidents.